Prediksi financial distress dalam mengukur kinerja perusahaan manufaktur - Eko Sulastri; Rachma Zannati (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2018)
This study aims to provide empirical evidence regarding the effect of Current Ratio, Total Asset Turn Over, Total Debt to Equity, and Net Profit Margin on Financial Distress measured using EPS (Earning per Share). The object of this study is the automotive and component manufacturing and textile and garment sector manufacturing companies listed on the IDX for the 2013-2017 period. Based on the purposive sampling method, based on predetermined criteria, 25 companies were selected as research samples. The analytical technique used is logistic regression. The results showed that the effect of Current Ratio, Total Asset Turn Over, positive had no effect on Financial Distress, while Total Debt to Equity, and Net Profit Margin were positive and significant towards Financial Distress